Kejadian mikropenis pada anak obes - Siswanto Basuki; Madarina Julia; Soeroyo Machfudz (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background : Obese children are more likely to have less testosterone, which may lead to disorder of penile development.Objectives : To assess the association between obesity in children and the occurrence of micropenis. Methods : TA cross sectional study was carried out in 36 obese and 28 non- obese pubertal male children (10-13 years old) and 49 obese and 36 non-obese prepubertal male children (4-7 years old). Obesity was defined as body mass index (BMI) equivalent to or above the 95th percentile of the CDC 2000 growth reference standard. Length of the penis was measured perpendicular to the surface of the os symphysis pubis to the tip of the glans penis. Skinfold thickness was measured on the area of mons pubis using a caliper. Volume of the testis was measured using an orchidometer. Results : The mean (SD) of penis length in 36 pubertal obese and 28 non-obese children were 5.56 (1.14) cm and 6.05 (1.37) cm, respectively; whereas the mean (SD) of penis length in 49 pre-pubertal obese and 39 non-obese children were 5.09 (0.76) cm and 5.36 (0.56) cm, respectively. There was significant difference in the mean (95% CI) length of penis in pubertal obese and non-obese children (p = 0.04). Fisher's exact test showed that the occurrence of micropenis was not associated with obesity, age, fat thickness on mons pubis, and volume of the testicles.Conclusion : There was no significant difference in the occurrence of micropenis, but there was significant difference in the mean length of penis in obese children and children with normal age-related body mass index.